Vegetative and reproductive plasticity of broccoli at three levels of incident photosynthetically active radiation - Francescangeli, Nora; Sangiacomo, Miguel Angel; Marti, Hector Ruben (2019)
To study the effects of shading on the growth, development, dry matter partitioning, and plant architecture of broccoli, "Legacy" hybrid plants were grown in pots in a greenhouse under black shading meshes to generate different levels of photosynthetically active radiation (PAR). The average incident PAR was 23 mol PPF square m/d under control conditions, 15.2 under a 35% mesh, and 6.7 under a 70% mesh. The air temperature was within the range 15-22 deg C. As shading increased so did the duration of the growth cycle and the leaf area (LA). Shading did not affect the number of leaves, although the upper ones were more erect. The stem length and the accumulated intercepted PAR (IPAR) were negatively related. Inflorescence diameter and commercial fresh weight decreased only with the 70% mesh. Shading did not affect stem dry weight (DW) but altered dry matter allocation in the root and spear. The DW of the leaves maintained an average 45.7% of the total DW despite the greater LA developed under shade. The net assimilation rate diminished with the reduction of IPAR, and the LA increased; the plant relative growth rate was therefore practically constant. With increased shading, the leaves and the stem became the dominant photosynthate sinks. The commercial fresh weight achieved with 15.2 mol photosynthetic photon flux (PPF) square m/d was equivalent to that obtained with 23 mol PPF square m/d, but the cycle was extended for 4.5 days. With 6.7 mol PPF square m/d, yield diminished because of the lower DW produced in a cycle extended by 15 days, and because more dry matter was allocated to the stem than to the spear. Based on these results, broccoli could be considered a shade-tolerant plant.